Kajian Tentang Keahlian dan Kesiapan Auditor SMK3 Dalam Melakukan Audit Faktor Bahaya dan Risiko Psikososial Pada ISO 45001:2018 - Dimas Angga Kharisma; Doni Hikmat Ramdhan (Universitas Ngudi Waluyo, 2019)
Psychosocial hazards and risks are recognized as a challenge for external auditors when auditing an Occupational Health and Safety Management System (SMK3) in an organization. The voluntary standard ISO 45001: 2018 published in March 2018 then requires explicitly the organization to identify psychosocial hazards. Audit is the organization's main tool for implementing SMK3 in measuring performance. So that this requires auditors to have expertise and readiness to fulfill the requirements of the ISO 45001: 2018. This study aims to examine the auditor's expertise in conducting psychosocial hazard audits in ISO 45001 SMK3 audits. This research is a descriptive study with cross sectional method, carried out by in-depth interviews with 7 professional auditors who actively conduct SMK3 audits and are IRCA certified auditors. The variables seen are expertise in identifying issues, expertise in conducting investigations when auditing, educational background, work, training, audit experience. Research shows that only only 14% have expertise and are ready for psychosocial auditing. The causes of unfulfillment of expertise and readiness are caused by the auditor's understanding of psychosocial hazards which causes weak expertise in identifying issues and investigations through document searches, records, observation and interviews, educational background, work and minimal training and training related to hazards and psychosocial risks , the need for extra time in investigating psychosocial hazards and risks, openness of the auditee, and the absence of specific methods or tools in conducting psychosocial audits in SMK3 audits.